Studies In fleshy and gelly fungi - Tremellales - and M.S. PATIL, S.H. MAHAMULKAR, B.D. KUNDALKAR (Indian Phytopathology, 2002)
In the present paper six new taxa belonging to five genera of the two families – Tremellaceae and Sebacinaceae of the order Tremellales have been presented. These are viz. Holtermania dimorphobasidiae sp.nov., Myxarium intermedius sp.nov., Efibulobasidium dimorphobasidiae sp.nov., E. patiliensis sp.nov., Pseudotremellodendron pusio (Berk.) Reid var. papillatus var.nov. and Sebacina microbasidiae Christ & Hauersl. var. indica var.nov. based on purely comparative morphological basis. Holtermania and Pseudotremellodendron are new records for India.